Evaluation of clinical efficacy of immediate implant placement into debrided infected sockets using demineralized freeze-dried bone allograft and platelet rich fibrin membrane: a clinical trial - Sharma, Deepali; Gupta, Ankita; Jha, Puja; Sachan, Swapnil; Kumar, Varun; Manhas, Kamaljeet; Vaid, Pulkit (International Journal of Clinical Trials, 2022)
Background: The aim of the study was to evaluate the clinical efficacy of demineralised freeze dried bone allograft (DFDBA) and platelet rich fibrin (PRF) membrane in immediate implant placement into debrided infected mandibular molar sockets. Methods: A clinical trial was conducted on 15 adult patients requiring tooth extraction and replacement with endosseous implants. Atraumatic tooth extraction was followed by thorough debridement of the socket prior to implant placement. Demineralized freeze dried bone allograft and PRF membranes were used for guided bone regeneration. Pain, signs of infection, vertical bone height measurements (IS-BIC) and stability of implants (torque values) were assessed using paired t test, analysis of variance (ANOVA) and Chi-square test. Results: Statistically significant reduction in pain from immediate post-operative (post-op) day to 1st post-op day, 7th post-op day to 4 months post-op (p=0.006) was seen. Infection was present preoperatively and absent post-op 1st day, 7th day and 4 month in all the subjects. The mean IS-BIC was 2.30±2.27 mm post-op and 0.75±0.74 mm at 4 months. Average height gain on mesial and distal side was 1.55 mm (p=0.009). Conclusions: With proper pre-op and post-op care, immediate implant placement along with DFDBA and PRF membrane in teeth exhibiting periapical pathology, is a cost effective, time saving and reliable treatment option.